The Influence of Instagram Social Media on Cyberbullying Behavior of Students in Class XI IS UPT SMA Negeri 3 Bulukumba - A.Octamaya Tenri Awaru; Anisa; Syarifah Aini; Diella Nirmala Sari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to find out the use and effect of Instagram social media on the students of XI IIS UPT SMA Negeri 3 Bulukumbang and how they responded to that phenomenon. This study uses quantitative research. The results of this study indicate that (1) the use of Instagram social media by students is 69,57% in the high category. And the usage indicator of Instagram social media with the highest percentage is Instagram as a median for obtaining various information (88%). And the most used feature is the saved feature (78%); (2) The students response to cyberbullying behavior is 55.7% in the middle category. And the percentage of response for cyberbullying behavior is giving advice to people who are racist on Instagram, which is 77%. (3) The effect of Instagram social media usage on cyberbullying behavior of class XI IIS UPT SMA Negeri 3 Bulukumba students The regression results show that the significance value is 0,02 < 0,05 and the value is 2,316 > 2,021 which means that the Instagram social media variable (X) influences the Cyberbullying behavior variable (Y).